2014
DOI: 10.1002/bmc.3248
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of interactions between methoxatin disodium salt and human serum albumin by pressure‐assisted capillary electrophoresis/frontal analysis and circular dichroism spectroscopy

Abstract: Pressure-assisted capillary electrophoresis (PACE)/frontal analysis (FA) and circular dichroism spectroscopy were utilized to investigate the interactions between methoxatin disodium salt (PQQ-2Na) and human serum albumin (HSA). With the PACE/FA method, sodium phosphate buffer solution (67 mm, pH 7.4) was used as the background electrolyte. Hydrodynamic injection at 50 mbar for 50 s and external pressure of 50 mbar were applied. The binding constant and the number of primary binding sites to HSA were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Table 5 showed different studies that have been reported over the years for the evaluation of the binding affinity of HSA of numerous drugs and other bioactive compounds using CE techniques. Many studies focused on the individual binding parameters for each compound/enantiomer [153,155,161] while others also described competitive studies between compounds to the binding sites of HSA [156,157,159]. Furthermore, most of these studies were enantioselective studies where the differences in binding of each enantiomer of the analyzed compounds to HSA were evaluated and compared using, many of them, HSA as a chiral selector [150,152,154,155].…”
Section: Capillary Electrophoresismentioning
confidence: 99%
“…Table 5 showed different studies that have been reported over the years for the evaluation of the binding affinity of HSA of numerous drugs and other bioactive compounds using CE techniques. Many studies focused on the individual binding parameters for each compound/enantiomer [153,155,161] while others also described competitive studies between compounds to the binding sites of HSA [156,157,159]. Furthermore, most of these studies were enantioselective studies where the differences in binding of each enantiomer of the analyzed compounds to HSA were evaluated and compared using, many of them, HSA as a chiral selector [150,152,154,155].…”
Section: Capillary Electrophoresismentioning
confidence: 99%
“…The displacement studies were performed by using several methods, including ultrafiltration [10], ED [11], crystallographic studies [12], CD [13], fluorescence spectroscopy [14, 15], molecular modeling [16], high‐performance affinity chromatography [17], and capillary electrophoresis (CE) in different modes including affinity CE, vacancy affinity CE, partial filling CE, near‐infrared dye‐displacement CE or CE‐FA [1, 1821]. Despite the fact that CE‐FA method is widely used for binding parameters determination only a few research groups reported about its applicability for displacement studies [22–29]. CE‐FA method was chosen for these measurements in view of its many benefits, which include small sample consumption, robustness and the possibility of high‐throughput screening [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…However, some disadvantages of these analytical techniques limit their applications, such as long equilibrium time and large sample consumption. Capillary electrophoresis (CE) has been proved to be more convenient and cost-effective for the interaction study [5,[12][13][14][15][16][17]. There are several modes of CE have been proposed for the quantitative assessment of drug-protein interactions, such as affinity capillary electrophoresis, the Hummel-Dreyer method, vacancy peak method, vacancy affinity capillary electrophoresis, and capillary electrophoresis-frontal analysis (CE-FA) [11,18].…”
Section: Introductionmentioning
confidence: 99%